An IMPDH2 variant associated with neurodevelopmental disorder disrupts purine biosynthesis and somite organization - Audrey G. O’Neill; Morgan E. McCartney; Gavin M. Wheeler; Jeet H. Patel; Gardenia Sanchez-Ramirez; Justin M. Kollman; Andrea E. Wills (Proceedings of the National Academy of Sciences, 2025)
IMP dehydrogenase (IMPDH) controls a key regulatory node in purine biosynthesis. Gain-of-function mutations in human IMPDH2 are associated with neurodevelopmental disorders and neuromuscular symptoms including dystonia, but the developmental mechanisms underlying these defects are unknown. We previously showed that these mutants are insensitive to GTP inhibition and hypothesized that their hyperactivity would affect nucleotide metabolism in vivo. Here, we characterize the metabolic and developmental consequences of the neurodevelopmental disorder-associated IMPDH2 mutant, S160del, in Xenopus tropicalis . We show that expressing S160del but not WT human IMPDH2 disrupts purine pools and somite organization in the developing tadpole. We also show that S160del disrupts in vivo IMPDH filament assembly, a well-described IMPDH regulatory mechanism. Cryo-EM structures show that S160del disrupts filament assembly by destabilizing the dimerization of regulatory Bateman domains. Dimerization of Bateman domains and subsequent filament formation can be restored with a high affinity ligand, but this does not restore sensitivity to GTP inhibition, suggesting S160del also disrupts allostery of IMPDH2 filaments. This work demonstrates that the structural effects of patient IMPDH2 variants can cause disruptions both to nucleotide levels and to the normal development of sensorimotor structures, helping us better understand the physiological basis of disease in these patients.